DEVELOPING A DIGITAL FLIPBOOK FOR FACILITATING READING ACTIVITY IN AN INCLUSIVE CLASS : An Innovative Approach to Enhance Reading Activity in Inclusive Education - Ketut Septia Anyawati; Prof.Dr. I G A Lokita Purnamika Utami, S.Pd., M.Pd,; I Ketut Trika Adi Ana (Jurnal Santiaji Pendidikan (JSP), 2026)
This research focuses on developing and validating a digital flipbook designed to enhance reading comprehension for sixth-grade students in inclusive classrooms, particularly those with special needs, such as students who are deaf or mute. Utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the study addresses the challenges faced by inclusive students in accessing reading media as material by incorporating accessibility features like sign language, subtitles, visuals, and animations. The research employed various instruments, such as a guide for interviews aimed at assessing needs, a separate interview guide for educators, another for students, a journal maintained by the researcher, a tracking sheet for product development progress, evaluations by content experts, assessments by media experts, and a questionnaire evaluating practicality. The digital flipbook was evaluated by content experts who rated it 4.75 out of 5, and media design experts who scored it 4.60 out of 5, both indicating a "very good" category. Additionally, the practicality of the digital flipbook was assessed by students and teachers, yielding scores of 4.6875 and 4.625, respectively, falling into the "very good" category. The study concludes that the digital flipbook is an effective media for enhancing the reading comprehension of inclusive students. It is user-friendly, engaging, and effectively improves comprehension. Given its high level of validity and practicality, the digital flipbook can serve as a model for other inclusive learning environments and has the potential to enhance the quality of inclusive education in Indonesia.